Non-accounting students’ perception on the development of study skills using in-class supplemental instruction / Shazalina Mohamed Shuhidan ... [et al.] - Mohamed Shuhidan, Shazalina; Awang, Yunita; Mohamed, Norazamina; Zainal @ Zakaria, Zaiza Norsuriati (2018)
Challenges such as different background and abilities of universities’ students, reluctance of academic staff in understanding students’ learning style and lack of study skills knowledge among students and lecturers are to be resolved by public universities. Resolving these challenges will provide better learning environment in public universities. Thus, the objectives of this study are to identify the reflective measures of study skills and to examine the students’ perception on the development of study skills by using In-Class Supplemental Instruction (ICSI). Using the questionnaires survey, this study found 10 reflective measures of study skills with Cronbach Alpha of 0.930 which indicates all reflective measures have good internal consistency reliability. The respondents are satisfied with the ICSI sessions in helping them to develop their study skills with an average mean of 4.09. It is concurred that ICSI approach assists in developing study skills such as deeper understanding, discussing and solving problem, teamwork and academic skills.